THE UNITED STATES’ MONETARY POLICY SPILLOVER EFFECT AGAINST RUPIAH -US DOLLAR EXCHANGE DURING USA – CHINA TRADE WAR - Setyadharma, Andryan; Rahmawati, Anisa (Jurnal Ekonomi Kuantitatif Terapan, 2022)
The United States (US) and China trade war has resulted in global economic crisis. This causes spillover effects to other countries due to the policies imposed by the two big countries. The objective of the research is to analyze the impact of Fed Fund Rate, as the monetary policy of the US, as well as other variables on the Rupiah -US Dollar Exchange Rate. The method used in this analysis is the Error Correction Model with time series data. The result indicates that in the long run the depreciation of Rupiah -US Dollar exchange rate is influenced by the increase of Fed Fund Rate, while there is no impact of Fed Fund Rate on Rupiah -US Dollar Exchange Rate in the short run. The results suggests that the US monetary policy during the trade war in form of the increase of Fed Fund Rate in long term has resulted spillover effect in Indonesia i.e., the depreciation of the Rupiah – US Dollar exchange rate.